STUDY ON USING DATA OF FATTY ACIDS IN BOTANICAL CLASSIFICATION (CHEMOTAXONOMY) FOR RED SEAWEED SPECIES - Thanh, Le Tat; Quan, Pham Minh; Anh, Nguyen Van Tuyet; Tien, Dam Duc; Sy, Do Trung; Hue, Pham Thu; Long, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2015)
In this paper, the compositions and contents of fatty acids in the total lipid extracts of 69 red seaweed samples belonging to 9 families (Gracilariaceae, Hypneaceae, Ceramiaceae, Bangiaceae, Hylamaniaceae, Bonnemaisoniaceae, Phyllophoraceae, Rhodymeniaceae and Halymeniaceae) are studied. According to the results, 56 fatty acids are identified, in which 12 fatty acids were considered “fatty acid markers” for the botanical classification (Chemotaxonomy) of red seaweed species such as C14:0, C15:0, C16:0, C16:1n-7, C18:0, C18:1n-9, C18:1n-7, C18:2n-6, C20:3n-6, C20:4n-6, C20:5n-3 and C22:0. By using principal component analysis method (PCA), the analysis result on two-dimensional chart showed that families of red seaweed are distributed into separate regions. Classification tree diagram of the red seaweed species based on essential fatty acid composition is also given.